Trapped by debt: an ethnographic study of medical indebtedness and hospital detention in the Fundong Health District, Cameroon - Ashangwa Constantine Tanywe; Ashangwa Constantine Tanywe; Ngambouk Vitalis Pemunta; Ngambouk Vitalis Pemunta; Vidarah Nimar; Cybel Nji Angwe; Mathias Alubafi Fubah; Mathias Alubafi Fubah; Maurine Ekun Nyok; Tom Obara Bosire; Nguyen Ngoc Bich Tram; Brendabell Ebanga Njee; et al. (Frontiers in Public Health)
BackgroundThis study investigates the structural and socio-cultural drivers of medical indebtedness and hospital detention due to unpaid healthcare bills in the Fundong Health District, Cameroon. It explores how poverty, institutional shortcomings, and cultural beliefs converge to exacerbate patients’ financial vulnerability and delay access to care.MethodsA qualitative anthropological approach was employed between February and November 2022, combining 34 in-depth interviews with extended ethnographic observation in hospital wards, billing offices, and family waiting areas. Data were analyzed using iterative grounded theory methods, including open, axial, and selective coding of interview transcripts, focus group discussions, and field notes. This methodology allowed for a nuanced understanding of how debt and detention are experienced and perpetuated. All data were transcribed, manually coded, and analyzed using NVivo 14 software to identify recurring themes related to hospital detention.ResultsThe findings show that medical indebtedness is driven by poverty, lack of health insurance, and limited social support. Institutional factors—including underfunded healthcare infrastructure and high user fees—compound these vulnerabilities. Cultural norms, such as beliefs discouraging financial preparation for illness, further heighten exposure to risk. The practice of hospital detention, though largely undocumented, imposes severe physical, emotional, and financial burdens, prompting some to delay care or adopt harmful coping mechanisms.Conclusion/policy implicationsAddressing medical debt and hospital detention requires a multifaceted policy response. Recommendations include eliminating maternal user fees, expanding health insurance coverage for vulnerable populations, protecting hospital-based social assistance, and replacing detention with legal safeguards and social mediation. Additionally, culturally sensitive financial literacy and mental health support programs are vital. Long-term investment in health infrastructure and governance is essential to reduce out-of-pocket spending and ensure equitable, rights-based healthcare access.